E-commerce Sebagai Salah Satu Bentuk Smart Village - Triani Arofah; Negina Kencono Putri (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2023)
Smart Village is currently being researched more intensively to do. With a concept oriented towards solving problems in the village so that it becomes a research issue that is easy to develop, essential points in Smart villages include smart economy. This research focuses on the development of e-commerce to support smart economy programs in smart villages. This research method related to e-commerce system development uses the SDLC (System Development Life Cycle) methodology. A uniform modeling language in design (UML) and system development using web-based programming. The results of this study in the form of a sales information system (e-commerce) for rural communities can be used as a means of information and communication between sellers and buyers in the area of a village. With the existence of this e-commerce system, it can indirectly increase the income of villagers